Royal College of Pathologists' accreditation pilot study: a year later. The College Audit Steering Committee. (1991)
Twenty one heads of departments who participated in the Royal College of Pathologists' pilot study of laboratory accreditation were questioned a year after the event to discover if the process had produced any lasting effect. All but one responded. Eighteen (90%) felt that there had been lasting and tangible benefit from their inspection. Of 10 departments with deficiencies relating to resources (and where no plans to upgrade existed before the study), five (50%) had obtained improvements as a direct result of the inspector's report. Overall, 16 (80%) of respondents were in support of the development of an accreditation scheme of the type attempted, and none were opposed. The envisaged scheme seems to have the potential to produce lasting improvements in service and commands the support of the departments involved so far.